Digital to Analog Facially Generated Interchangeable Facebow Transfer: Capturing a Standardized Reference Position. (21st March 2022) - Kois, John C.; Kois, Dean E.; Zeitler, Jonathan M.; Martin, Jean
Abstract: Although the evolution of digital technology continues to improve patient data acquisition, the ability to both standardize the recording of the maxillary occlusal plane and capture the necessary dynamic data for dento‐facial analysis remains elusive. This article describes step‐by‐step techniques to position the maxilla on an articulator using the natural head position and a facial reference system (Kois Facial Reference Glasses) for both analog and digital workflows. A photographic technique will be presented that captures the natural head position and allows the clinician to align a 2D reference photograph with the maxillary intraoral digital scan and the virtual articulator. Using this reference photograph, the clinician can record and communicate to the technician the maxillary arch position in relationship with the facial references, as well as transfer the additively manufactured casts in the same facial orientation for mounting and analysis either virtually or on an analog articulator.